The relationship between patients' perception of type 2 diabetes and medication adherence: a cross-sectional study in Japan - Kana Hashimoto; Koki Urata; Ayano Yoshida; Reiko Horiuchi; Naoto Yamaaki; Kunimasa Yagi; Kunizo Arai (BMC, 2019)
Abstract Background The self-management of type 2 diabetes mellitus (T2DM), which involves adherence to medical instructions on diet and nutritional advice, physical activity, medication regimen, and weight and stress management, is necessary for the treatment of T2DM. In this study, we investigated the relationship between patients' perceptions of their disease and their adherence to their medications. And we attempted to determine whether distinct subphenotypes of behavioral change of medication adherence can be discerned based on a patients' perceptions. Method A cross-sectional study using a questionnaire was conducted among 157 patients with T2DM from October 2015 to September 2017. Questionnaires were administered to assess the participants' demographic and clinical characteristics, medication adherence, diabetes knowledge, and perception of being diabetic. Principal component analysis (PCA) and cluster analyses were performed to classify medication adherence patterns in the total cohort. Multiple regression analyses were performed to identify the determinant factors of medication adherence. Results PCA showed the interpretable medication adherence of patients with diabetes by using component 1 ("accessibility to medical treatment") and component 2 ("status of taking medicines"). We identified four groups that show significantly different medication adherence by using cluster analysis on the basis of the two components. Multiple regression analysis showed that body mass index (BMI), family history of diabetes, one factor of patient's perception (living an orderly life), and diabetes knowledge were found to be significant predictors of medication adherence in patients with T2DM. Conclusions In patients with T2DM, the patient's diabetes perception of "living an orderly life" is associated with medication adherence. A poor adherence group may be able to change their adherence to diabetes treatment by developing the perception of "living an orderly life."